The detection of internal tandem duplication in the FMS-like tyrosine kinase 3 gene in a sample of Iraqi patients with acute myeloid leukemia - Lafta, Shurooq A.; Abdulhassan, Ismail A. (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. Acute myeloid leukemia (AML) is a genetically heterogeneous malignancy significantly influenced by FMS-like tyrosine kinase 3 mutations. This study investigated the prevalence and clinical implications of internal tandem duplication (ITD) mutations in FLT3 in patients with AML in Iraq. Material and methods. The study involved blood samples collected from 50 newly diagnosed AML and 50 healthy subjects between April 2023 and January 2024 and used for conventional PCR. PCR products positive for the ITD mutation were subjected to fragment analysis using capillary electrophoresis (CF) to confirm ITD mutations. Results. FLT3-ITD mutations were identified in 20% of patients with AML (10/50), with striking female predominance (90% of mutation-positive cases). Based on the FAB classification, M5 was the most prevalent FAB subtype among mutation carriers (40%), with no mutations detected in M7. Conclusion. This study provides critical information on the prevalence and clinical implications of FLT3-ITD mutations in patients with AML in Iraqi, emphasizing the need for precise molecular diagnostic approaches. This finding revealed a distinct subset of patients with AML that harbor FLT3-ITD mutations, with a significant proportion exhibiting elevated allelic ratios, which reinforces their prognostic relevance.